Structural basis for the tethered peptide activation of adhesion GPCRs - Ping, Yu-Qi; Xiao, Peng; Yang, Fan; Zhao, Ru-Jia; Guo, Sheng-Chao; Yan, Xu; Wu, Xiang; Zhang, Chao; Lu, Yan; Zhao, Fenghui; Zhou, Fulai; Xi, Yue-Tong; et al. (Nature (London), 2022)
Adhesion G-protein-coupled receptors (aGPCRs) are important for organogenesis, neurodevelopment, reproduction and other processes 1 – 6 . Many aGPCRs are activated by a conserved internal (tethered) agonist sequence known as the Stachel sequence 7 – 12 . Here, we report the cryogenic electron microscopy (cryo-EM) structures of two aGPCRs in complex with G s : GPR133 and GPR114. The structures indicate that the Stachel sequences of both receptors assume an α-helical–bulge–β-sheet structure and insert into a binding site formed by the transmembrane domain (TMD). A hydrophobic interaction motif (HIM) within the Stachel sequence mediates most of the intramolecular interactions with the TMD. Combined with the cryo-EM structures, biochemical characterization of the HIM motif provides insight into the cross-reactivity and selectivity of the Stachel sequences. Two interconnected mechanisms, the sensing of Stachel sequences by the conserved ‘toggle switch’ W 6.53 and the constitution of a hydrogen-bond network formed by Q 7.49 /Y 7.49 and the P 6.47 /V 6.47 φφG 6.50 motif (φ indicates a hydrophobic residue), are important in Stachel sequence-mediated receptor activation and G s coupling. Notably, this network stabilizes kink formation in TM helices 6 and 7 (TM6 and TM7, respectively). A common G s -binding interface is observed between the two aGPCRs, and GPR114 has an extended TM7 that forms unique interactions with G s . Our structures reveal the detailed mechanisms of aGPCR activation by Stachel sequences and their G s coupling. Adhesion GPCRs involved in cell and matrix interactions signal through a distinct self-cleavage, self-activation mechanism.